2019
DOI: 10.1007/s12264-019-00420-6
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Placebo Analgesia Model in Rats with Inflammatory Pain

Abstract: With the shifting role of placebos, there is a need to develop animal models of placebo analgesia and elucidate the mechanisms underlying the effect. In the present study, male Sprague-Dawley rats with chronic inflammatory pain caused by complete Freund's adjuvant (CFA) underwent a series of conditioning procedures, in which morphine was associated with different cues, but they failed to induce placebo analgesia. Then, conditioning with the conditioned place preference apparatus successfully induced analgesic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…It should be noted that a single conditioning mechanism is insufficient to account for nocebo effects. These models, on the other hand, are all based on healthy animals, possibly due to the difficulties of inducing nocebo effects in diseased animals 28 . However, the fact is that nocebo effects are inextricably linked with illness states.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that a single conditioning mechanism is insufficient to account for nocebo effects. These models, on the other hand, are all based on healthy animals, possibly due to the difficulties of inducing nocebo effects in diseased animals 28 . However, the fact is that nocebo effects are inextricably linked with illness states.…”
Section: Discussionmentioning
confidence: 99%
“…Another major unsolved obstacle is that placebo analgesia in rodents has been consistently shown in acute pain models, but is highly unreliable in chronic pain models. For example, McNabb et al did not observe any placebo analgesia in a rat model of chronic neuropathic pain using spinal nerve ligation (SNL), and Yin et al failed to elicit placebo analgesia in a CFA-induced long-lasting inflammatory pain model 15,16 . On the other hand, Zeng et al found that 36% of rats showed placebo responses following SNL 17 .…”
Section: Main Textmentioning
confidence: 99%
“…TWL was tested with Hargreaves's method (Yin et al, 2020). Briefly, rats were placed on the surface of the Thermal Stimulator System (ZH-200, Anhui Zhenghua Instrument Equipment Co., Ltd.), and adapted in a quiet environment for 15 min.…”
Section: Thermal Withdrawal Latency (Twl) Testmentioning
confidence: 99%